2012
DOI: 10.1016/j.tox.2011.11.017
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of manganese on acetylcholinesterase activity enhances oxidative stress and neuroinflammation in the rat brain

Abstract: Background Manganese (Mn) is a naturally occurring element and an essential nutrient for humans and animals. However, exposure to high levels of Mn may cause neurotoxic effects. The pathological mechanisms associated with Mn neurotoxicity are poorly understood, but several reports have established it is mediated, at least in part, by oxidative stress. Objectives The present study was undertaken to test the hypothesis that a decrease in acetylcholinesterase (AChE) activity mediates Mn-induced neurotoxicity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(62 citation statements)
references
References 84 publications
7
54
0
Order By: Relevance
“…At high substrate concentrations, it probably is displaced from α-site to only occupy the β-site, therefore causing activation [22]. , the results here corroborate other works [25,26]. Al 3+ didn't appear among the groups of ions reported by…”
Section: Discussionsupporting
confidence: 91%
“…At high substrate concentrations, it probably is displaced from α-site to only occupy the β-site, therefore causing activation [22]. , the results here corroborate other works [25,26]. Al 3+ didn't appear among the groups of ions reported by…”
Section: Discussionsupporting
confidence: 91%
“…Although the concentration of Cd was below the established level set by the Brazilian legislation, Cd is a human carcinogen, a potent endocrine disruptor, and exerts toxic effects on kidney, skeletal, respiratory, and reproductive systems (Gerbron et al 2015;Jiménez-Ortega et al 2012;Wang et al 2014;WHO 2011). Mn and Pb can inhibit AchE (Santos et al 2012), and mixtures of Pb + Cd (detected in SC) can induce neuronal degeneration in the brain even at low concentrations (Cobbina et al 2015).…”
Section: Physicochemical Parameters Are Not Enough To Predict the Chementioning
confidence: 99%
“…Similar conflicting results were found in the effect of Mn on AChE. In studies that used prolonged Mn exposure, Mn caused a reduction in AChE activity [129,137,138]. On the other hand, high sub-acute Mn doses resulted in elevations in AChE activity [128,139,140].…”
Section: Mn Toxicitymentioning
confidence: 88%
“…Santos et al found a dose-dependent increase prostaglandin and isoprostanes post MnCl2 injections in rats [129]. Also, Fernsebner et al…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation